Assessing Protected Area Zoning Effectiveness With Remote Sensing Data: The Case of Nahuel Huapi National Park, Argentina - Rivarola, María Daniela; Dein, Jacob; Simberloff, Daniel; Herrero, Hannah Victoria (Frontiers in Remote Sensing, 2022)
Protected areas (PAs) remain the most important tool to prevent biodiversity loss and habitat degradation worldwide, but the formal creation of a PA constitutes only the first step. In recent decades, concerns about PA effectiveness have arisen, and several PAs have been evaluated using different methods. Results show that while some PAs are achieving their conservation goals, others have been less effective. Particularly, assessing broadscale outcomes is a method that allows us to monitor change over time at a large scale, using remote sensing data. In this study, we evaluated the effectiveness of Nahuel Huapi National Park, with particular attention to its three protection categories: Strict Natural Reserve (SNR), National Park (NP), and National Reserve (NR) (IUCN categories Ia, II, and VI respectively). We compared changes in Normalized Difference Vegetation Index (NDVI) among sites in these categories and between them and neighboring unprotected areas, over the period 2000-2020. Overall, habitat degradation was low, and we found no difference among the four categories evaluated. Nevertheless, a greening process has been conspicuous in the entire area, with higher values both in the SNR and in the unprotected area. We propose possible explanations as we take into account variables such as dominant tree species, precipitation, temperature, elevation, and wildfires. This study supports the importance of NHNP at the regional and national levels, particularly its SNR areas.